Aplicación del software libre edubuntu y su aporte en el rendimiento académico en los estudiantes de décimo año de Educación Básica, del Colegio Fiscal Técnico Balao del cantón Balao, durante el periodo lectivo 2012-2013. - Vega Reyes, Roberto Carlos (2016)
The main purpose of this research work is to convey to teachers the importance of Edubuntu operating System, as a teaching resource in the teaching-Learning process to generate on students on students significant and lasting knowledge, demonstrating that disinterest and lack of knowledge generate difficulties on students’ learning and poor performance on the students of Math and Language too. Under this analysis, this research will take place at the Técnico Balao high school of Balao canton in the Guayas province , where a workshop about “ the use of Edubuntu Operating System “ with the purpose all teachers know and use the different applications, in order to improve their academic performance of the students in the Tenth year of basic education, school year 2013-2014 which allows the development of the purpose guided to provide to teachers some necessary strategies for developing their classes to value the students´ conceptual, procedural and attitudinal knowledge giving them an opportunity to develop their skills and capacities during the teaching-learning process. Finally I want to emphasize the importance of education on the human being as the only tool for the development and a better coexistence in the society, only in or hands is to offer a better country to the new generations demystifying to our students who from their way will contribute with proposal of solutions to the needs of their community.